Absenteeism economically considered - Vereker, John P. (Statistical and Social Inquiry Society of Ireland, 1851)
Gentlemen,?In addressing you this evening, I am anxious to confine myself as much as possible to absenteeism considered as a mere question of pounds, shillings, and pence, and as it affects the transfer of wealth from one country to another. I propose to examine the truth of the two conflicting theories, by which some economists maintain that every pound sent away, in the shape of absentee rent, is a complete loss or annihilation of that portion of the income or capital of the country; and by which others assert that so far as her wealth and prosperity are concerned, it is a matter of indifference whether a few or the whole of her wealthy inhabitants desert her shores, and reside abroad. But in treating of this question, I find it almost impossible to confine myself within those narrow bounds, and to do at the same time anything like justice to the subject; for many other considerations purely economical are involved in the question, in a manner that at first sight is apt to escape our observation. For instance, in our calculations of the losses a country sustains by absenteeism, we are entitled to take into account its effects upon the progress of manufactures, and to presume that peace and security for property exist, without which manufactures cannot prosper; and if on examination it appears that non-residence is a cause or promoter of insecurity, we are entitled to take into account the evils that consequently result, as well as the expense it entails upon the country, in the support of additional military and police?in the enforcement of justice, and the punishment of offenders. These subjects must be examined before we can estimate the mere economic evils of absenteeism; and to them and other similar circumstances it will be necessary to allude occasionally in as brief a manner as possible, for I feel that I should otherwise leave the portion of the subject most important, even as an economic question, untouched; and in doing so, I shall strictly observe the most salutary of all our rules?that which prohibits the introduction of any sectarian or political topic into this society.
Read December 17th 1849
Keywords: Absentee landlords; Poverty; 314.15